Kama muta: conceptualizing and measuring the experience of being moved across 19 nations and 15 languages - Zickfeld, J. H.; Schubert, T. W.; Seibt, C.; Blomster, J.; Arriaga, P.; Basabe, N.; Blaut, A.; Caballero, A.; Carrera, P.; Dalgar, I.; Ding, Y.; Dumont, K.; et al. (Emotion, 2019)
English-speakers sometimes say that they feel moved to tears, emotionally touched, stirred, or that something warmed their heart; other languages use similar passive contact metaphors to refer to an affective state. We propose and measure the concept of kama muta to understand experiences often given these and other labels. Do the same experiences evoke the same kama muta emotion across nations and languages? We conducted studies in 19 different countries, five continents, 15 languages, with a total of 3542 participants. We tested the construct while validating a comprehensive scale to measure the appraisals, valence, bodily sensations, motivation, and lexical labels posited to characterize kama muta. Our results are congruent with theory and previous findings showing that kama muta is a distinct positive social relational emotion that is evoked by experiencing or observing a sudden intensification of communal sharing. It is commonly accompanied by a warm feeling in the chest, moist eyes or tears, chills or piloerection, feeling choked up or having a lump in the throat, buoyancy and exhilaration. It motivates affective devotion and moral commitment to communal sharing. While we observed some variations across cultures, these five facets of kama muta are highly correlated in every sample, supporting the validity of the construct and the measure.